Pharmacoeconomic analysis of Oral and Injectable Proton Pump Inhibitors available in India - Pradnya Deolekar; Kavitha Vivek Dongerkery; Pramila Yadav; Jyoti Sonawane (Tehran University of Medical Sciences, 2023)
Introduction: Proton pump inhibitors (PPIs) effectively suppress acid secretion and play an essential role in peptic ulcer disease and gastroesophageal reflux disease. There is a genuine concern about overutilizing PPIs, leading to significantly high costs and undesirable outcomes. An increase in the patient medication cost was associated with decreased adherence to prescription medication. Hence, this study assessed the cost variation of proton pump inhibitors (PPI) drugs. Methods: The cost of different brands of commonly used PPIs was sorted out by referring latest "Monthly Index of Medical Specialties" October - December 2021, and 1mg online pharmacy. The cost of 10 dosage forms (Tablets/capsules) in INR of each brand, Cost Ratio, and Percentage Cost Variation for individual drug brands was calculated in the case of an oral drug, and the cost of one vial or ampoule was noted in the case of injectable drug. At last, the cost ratio and percentage cost variation of various brands was compared. Results: The data analysis showed a significant variation in the costs of different brands of proton pump inhibitors available In the Indian market. Percentage variation in cost for oral preparations of proton pump inhibitors marketed in India was found to be tablet/capsule Rabeprazole 20mg (1540%), Omeprazole 20 mg(718.18%), Pantoprazole  40mg (504.16%), Esomeprazole 20mg (173.68%), Lansoprazole 15 mg (84.90 %), Omeprazole  40 mg (60.34%) and with injectable preparations IVR abeprazole 20mg (1090.90%), Omeprazole  40 mg  (347.36%), Esomeprazole 40mg (216.66%), Pantoprazole 20mg (164.44 %), Pantoprazole 40mg (51.16%). Conclusion: There is a wide variation in the prices of proton pump inhibitors available in the market. Regulatory authorities, pharma companies, and physicians should maximize their efforts to reduce the cost of drugsThe need to search for reliable process indicators for the effectiveness of anti-diabetic therapy has been expressed in the literature. Process indicators have been described as essential processes that contribute to achieving outcomes